Co-composting of oil palm mesocarp fiber and palm oil mill effluent anaerobic sludge - Lim, Siong Hock (2011)
Utilization of oil palm mesocarp fiber (OPMF) in an alternative way as composting substrate for biocompost production was studied. Palm oil mill effluent (POME) anaerobic sludge is used as the nitrogen source and microbial seeding for the cocomposting process. The windrow composting system was applied in this study due to lower operation cost and higher flexibility in controlling. In physicochemical study, POME anaerobic sludge additions promoted thermophilic condition (50 – 68°C) in compost piles and maintain moisture content around 50 - 60%. The pH was slightly alkaline throughout composting process. However, the compact and oily properties of OPMF have limited oxygen transfer (below 10 mg/L) and water absorption in the substrates, thus requiring extensive turning and mixing in composting piles for optimum composting process. The final compost with final C/N ratio of 12.6 and high nutrients content is obtained after 50 days composting. For microbial succession study during composting process, polymerase chain reaction– denaturant gel gradient electrophoresis (PCR-DGGE) analysis was carried out. The molecular finger printing analysis indicated that the dominant microbe communities shifted from Pantoea and Termitomyces at the beginning of the composting process to Proteobacteria like Cupriavidus gilardii and Ralstonia basilensis. It has been observed that strong hydrolytic microbes were dominant in thermophilic phase of composting process. For structural degradation study in composting material,scanning electron microscopic (SEM) revealed the penetration of microbial community and removal of silica body on composting material. The microbial penetrations disrupted the hard surface of OPMF and promote the exposure of more easily degradable compound for active metabolic activity. After all, OPMF and POME anaerobic sludge co-composting make a good combination for substrates degradation. The nitrogen sources in sludge support microbial growth and a number of active degrader microbes have been identified. The removal of oily substance has been suggested capable in accelerating composting process.